Theological Education between the University and the Church: Durham University and the Common Awards in Theology, Ministry and Mission. Issue 1 (16th December 2013) - Higton, Mike
Abstract : This article examines the new 'Common Awards' partnership between the Church of England and Durham University, and asks what the university and the church have to gain from one another in the area of theological education. I argue that the university can help extend the range of critical conversations in which the church engages, and help form some of the intellectual virtues required in those who pursue this reflection. In return, the church can help the university to recognize its nature as a school of intellectual virtue, its need for insistent and pervasive discussion of the good that it does in the world, and its need to resist the pressures that threaten to thin its life down to technocratic rationality. I also argue that, for both the church's purposes and the university's purposes, the learning pursued in this partnership needs to be understood as deeply engaged with the life and practice of the church-as taking off from attentive description of that practice, and as returning to the refinement, extension and transformation of that practice, however long might be the journeys of abstraction and reflection that take place in between.